- #1

- 141

- 0

10b + 5be - 3e + 7c

10b + 5be - 3e = 7c

5be - 3e = 7c - 10b

e(5b - 3) = 7c - 10b

e = 7c - 10b / 5b - 3

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Gringo123
- Start date

- #1

- 141

- 0

10b + 5be - 3e + 7c

10b + 5be - 3e = 7c

5be - 3e = 7c - 10b

e(5b - 3) = 7c - 10b

e = 7c - 10b / 5b - 3

- #2

Mark44

Mentor

- 35,624

- 7,499

You're not starting with an equation! Without the first line below being an equation, you can't solve for anything.I need to rearrange this formula to make e the subject. Have I done it correctly?

Assuming that this is your starting equation -- 10b + 5be - 3e = 7c -- your work following it is fine, EXCEPT that you need to use parentheses. You should write e this way:10b + 5be - 3e + 7c

10b + 5be - 3e = 7c

5be - 3e = 7c - 10b

e(5b - 3) = 7c - 10b

e = 7c - 10b / 5b - 3

e = (7c - 10b) / (5b - 3)

- #3

- 141

- 0

Thanks a lot Mark

- #4

- 9

- 0

You're not starting with an equation! Without the first line below being an equation, you can't solve for anything.

Assuming that this is your starting equation -- 10b + 5be - 3e = 7c -- your work following it is fine, EXCEPT that you need to use parentheses. You should write e this way:

e = (7c - 10b) / (5b - 3)

Well if we assume that the first line is an equation (set equal to zero): 10b + 5be - 3e + 7c=0, then the second line changes:

10b + 5be - 3e = -7c, and that would change the rest of the steps which follow...

Share:

- Replies
- 5

- Views
- 7K